MURRAYA KOENIGI-A BOON IN DIFFERENT PATHOLOGICAL CONDITIONS - Chibueze, Igwe J.; V, Emenike I (Universal Journal of Pharmaceutical Research, 2016)
Since very long period of time medicinal plants or their bioactive compounds have been utilized by majority of world population particularly in developing countries for primary and traditional healthcare system. At present scenario, people are more interested to use herbal drugs because they are considered as safe and inexpensive having no adverse effects. Different parts of the plants like roots, leaves, stem, bark, fruits and seeds have been used in treatment of different diseases and strengthening the immune system. Murraya koenigii, is a herb from mainly Asian origin, it has therapeutic applications such as in bronchial disorders, piles, vomiting, skin diseases, night blindness, dysentery, diarrhoea, bites of poisonous animals, bruises and eruption etc. The present review is an attempt for description of M. koenigii, its phytochemical constituents and various pharmacological activities. Peer Review History: Article received on- 28 September 2016; Revised on- 3 November; Accepted on- 11 December; Available online 15 January 2017 Academic Editor: Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com Reviewer(s) detail: Dr. Masoumeh Divar , Shiraz University, Shiraz, Iran, zhaledivar@gmail.com Dr. Mohamed Salama , Modern University for Technology & Information, Egypt, salama47@yahoo.com